Dva sobolishki - Petro Milimov; Andrey Filchenko; Julia Kurganskaja; Maria Tonoyan; Olga Potanina; Sergej Kovylin (Andrey Filchenko, 2012)
Eastern Khanty Comprehensive Documentation & Analysis of two Endangered Siberian Languages: legacy data and last speakers of Eastern Khanty and Southern Selkup